Egg yolk antibody combined with bismuth-based quadruple therapy in Helicobacter pylori infection rescue treatment: a single-center, randomized, controlled study - Cheng, Sha; Li, Huan; Luo, Ju; Chi, Jingshu; Zhao, Wenfang; Lin, Jiahui; Xu, Canxia (Frontiers in Microbiology, 2023)
Background: The increasing antibiotic resistance is the main issue causing Helicobacter pylori (H. pylori) eradication failure. As a nutritional supplement, Egg Yolk Antibody (Ig Y) provides a new approach for H. pylori infection rescue therapy. Methods: In this randomized, controlled study, 100 H. pylori-positive patients with previous H. pylori eradication treatment were included. All individuals received standard bismuth-containing quadruple therapy twice daily (5 mg ilaprazole, 100 mg doxycycline, 500 mg clarithromycin or 1 g amoxicillin or 100 mg furazolidone and 220 mg colloidal bismuth tartrate) for 14 days and were randomized to receive either twice daily 7 g Ig Y-H. pylori treatment (study group) or not (control group). Four weeks after the end of treatment, urea breath tests were used to assess the H. pylori eradication rate. All participants scored by the Global Overall Symptom scale (GOS) and recorded adverse events during the trial. Results: The H. pylori eradication rates were 84.0% (95% CI 73.5%-94.5%) vs. 80.0% (95% CI 68.5%-91.5%) in the study and control groups at intention-to-treat (ITT) analysis and 85.7% (95% CI 75.6%-95.9%) vs. 80.0% (95% CI 68.5%-91.5%) at per-protocol (PP) analysis, respectively. The number of over 80% symptom relief after treatment in the two groups was 27 (60%) and 12 (29.2%) (p < 0.05), and the incidences of adverse events were 4 (8%) and 6 (12%), respectively. Conclusion: Both groups achieved satisfactory eradication efficiency in H. pylori rescue therapy and Ig Y-H. pylori effectively alleviates the symptoms with good compliance and fewer adverse effects.